La particitation numérique dans les slogans du hirak algérien - Kahina Ait Allaoua (Multilinguales)
This article is the extension of a previous publication on the use of particitation as a thesaurus in the protest speech of Algerian demonstrators during the popular movement of February 22nd, 2019. This present study will take up the concept of particitation initiated by Maigueneau, while considering the digital language as the thesaurus which feeds in the background the militant discourse in the slogans of the young Algerian demonstrators. Thus, through a socio linguistic, enunciative and pragmatic study ; we will show that the use of computer code in these statements is not only the expression of a quest for recognition of a social category, but also a new means of mobilization.